2016
DOI: 10.1016/j.addr.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin and endorepellin: A common route of action for similar angiostatic cancer avengers

Abstract: Traditional cancer therapy typically targets the tumor proper. However, newly-formed vasculature exerts a major role in cancer development and progression. Autophagy, as a biological mechanism for clearing damaged proteins and oxidative stress products released in the tumor milieu, could help in tumor resolution by rescuing cells undergoing modifications or inducing autophagic-cell death of tumor blood vessels. Cleaved fragments of extracellular matrix proteoglycans are emerging as key players in the modulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 277 publications
(344 reference statements)
0
90
0
Order By: Relevance
“…Given its widespread distribution [124,125] and its ability to interact with various molecules perlecan regulates various biological processes. Either via the protein core or the heparan sulfate chains, perlecan binds other ECM components as laminin, fibronectin and ECM1 and several growth factors including Fibroblast Growth Factor 1 (FGF-1), FGF-2, FGF-7, FGF-9 and FGF-18, FGF-binding protein, Platelet-Derived Growth Factor (PDGF), Hepatocyte Growth Factor (HGF), activin A, VEGF and progranulin [126,127,128,129,130,131,132]. The central role of perlecan in angiogenesis has been demonstrated by several independent studies and in various in vitro and in vivo models [133,134,135].…”
Section: Proteoglycans: Complex Functions From the Protein Core Anmentioning
confidence: 99%
“…Given its widespread distribution [124,125] and its ability to interact with various molecules perlecan regulates various biological processes. Either via the protein core or the heparan sulfate chains, perlecan binds other ECM components as laminin, fibronectin and ECM1 and several growth factors including Fibroblast Growth Factor 1 (FGF-1), FGF-2, FGF-7, FGF-9 and FGF-18, FGF-binding protein, Platelet-Derived Growth Factor (PDGF), Hepatocyte Growth Factor (HGF), activin A, VEGF and progranulin [126,127,128,129,130,131,132]. The central role of perlecan in angiogenesis has been demonstrated by several independent studies and in various in vitro and in vivo models [133,134,135].…”
Section: Proteoglycans: Complex Functions From the Protein Core Anmentioning
confidence: 99%
“…That is to say, it is possible that vessel formation might be controlled in different ways when angiogenesis is acting as the “enemy” such as in cancer or in pathologies such as diabetic retinopathy (28), compared with situations like fracture healing where angiogenesis is the “friend” (29). Considering the large body of evidence now linking Dcn inhibition of angiogenesis to autophagy (30,31), we can not ignore the fact that Bgn could regulate autophagy during fracture healing. Indeed in this regard it is interesting to note that endostatin induces autophagy in endothelial cells by modulating Beclin 1 and beta-catenin (32).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, hydrolysis of types XV and XVIII collagens results in the generation of endostatin, an inhibitor of angiogenesis [110,111,112], and the cleavage of the α3 chain of type IV collagen by MMPs releases the fragment tumstatin, which is a potent anti-angiogenic molecule [113,114]. Another BM-derived fragment is endorepelin, the C-terminal fragment of perlecan, which also exerts anti-angiogenic activity [115]. Since SVMPs release fragments of all of these proteins in the exudates [15,24,40,41,48], it is suggested that some of them exert anti-angiogenic activity and influence the tissue repair process.…”
Section: Hydrolysis Of Ecm Proteins Alters Cell-matrix Interactionmentioning
confidence: 99%